Packaging atmospheres alter beef tenderness, fresh color stability, and internal cooked color - Grobbel, J.P.; Dikeman, Michael E.; Milliken, George A.; Hunt, Melvin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Several meat quality traits affect consumers’ overall purchase decisions and satisfaction with meat products, but color is the major factor affecting purchasing decisions. According to some researchers, tenderness is the most important palatability attribute in consumers’ overall eating experience. Case-ready packaging in the meat industry is growing at a rapid rate and generally includes modified atmosphere packaging (MAP) with specific gases. Advantages of MAP include use of a centralized location, improved sanitation control, more consistent products, and increased marketing flexibility. Packaging beef in highoxygen (HiO2) MAP results in a desirable bright red lean color but can have detrimental effects on other quality traits, including increased off-flavors and decreased tenderness. Use of carbon monoxide (CO) has been approved by USDA and the Food and Drug Administration for use at levels up to 0.4% in retail MAP. Products in MAP that include CO have improved beef color stability and extended display time. Premature browning, originally discovered in ground beef, results when meat is cooked to temperatures lower than what is necessary to kill harmful pathogens but appears well done internally. This phenomenon is also found in whole muscle steaks and can be attributed to packaging environments, including HiO2 MAP. Therefore, objectives of our study were to evaluate the effects of different gas compositions in different MAP systems vs. vacuum packaging on grain finished beef tenderness, display color stability, and internal cooked color.
Keywords: Beef; Cattle; modified atmosphere packaging (MAP)